Impact of organisational practices on the relationships between young people with disabilities and paid social support workers. (November 2021) - Fisher, Karen R; Robinson, Sally; Neale, Kate; Graham, Anne; Johnson, Kelley; Davy, Laura; Hall, Edward C
Summary: This article uses Ikäheimo's concept of institutionally mediated recognition to explore how organisational norms and rules facilitate and constrain interpersonal recognition between a young person with disabilities and their paid support worker. The experience of recognition is important because it reflects the quality of this relationship and shapes the identity of both people in the paid support relationship. To understand the relationships between the pairs, Honneth's interpersonal modes of recognition were applied as the theoretical lens. The data were generated from photovoice, social mapping, interviews and workshops with 42 pairs of young people and their support workers in six organisations. These data were then analysed for the ways institutional practices mediated the interpersonal relationships. Findings: The findings revealed four practices in which the organisational context mediated interpersonal recognition: the support sites, application of organisation policies, practices to manage staff and practices to organise young people's support. Some organisational practices facilitated recognition within the relationships, whereas others were viewed by the pair or managers as constraints on conditions for recognition. Some young people and support workers also exercised initiative or resisted the organisational constraints in the way they conducted their relationship. Applications: The findings imply that to promote quality relationships, organisations must create the practice conditions for recognition, respond to misrecognition, and encourage practices that make room for initiative and change within the paid relationship. This requires supervision and training for and by support workers and people with disability.